(untitled) (Journal of Hama University, 2024)
This research aimed to explore the effect of the random exercise styles on acquiring and retaining some basic skills in gymnastics. The researcher has used the experimental approach using the experimental group style for its suitability the nature of the research, where the sample was of (20) males students of the faculty of physical education in Hama university, their ages ranged from 18-19 year. It has been chosen standardized tests to measure the studied skills in the research (forward roll, hand balance, head balance, side wheel). The results showed a positive effect to the random exercise style on acquiring and retaining studied skills. In light of study’s results, it was recommended to conduct research that integrate the random exercise style with others styles and studying the impact of this procedure on the acquisition and retaining the skills of gymnastics or others skills.